Sistem Antar Jemput Penonton dalam Penyelenggaraan MotoGP Mandalika (Studi Kasus pada Penonton MotoGP Mandalika asal Lombok dan Yogyakarta) - Lalu Jatmiko Jati; Rini Anggriani; Lady Faerrosa; Zahrah Zahrah (Target : Jurnal Manajemen Bisnis, 2022)
This study aims to explore in depth the audience's response to the Mandalika 2022 MotoGP title regarding the service and shuttle system for the official Mandalika Circuit bus. This research uses a qualitative approach with the type of case study research. The selection of research subjects was carried out using a purposive sampling technique, namely the Mandalika MotoGP audience from Lombok and the Special Region of Yogyakarta (DIY) who came to watch the Mandalika Circuit Lombok live. Methods of data collected by using interviews, observation, and documentation. Data analysis was carried out through the stages of data reduction, data display, and verification and drawing conclusions. The validity of the data was tested using the triangulation method. The results showed that: (1) All respondents admitted that they were disappointed with the organizers or committees who did not pick them up at the pick-up location in front of the Mandalika Circuit entrance as they should. (2) All respondents admitted that they had told their negative experiences to their relatives, co-workers, and family. (3) All respondents admitted that they will not watch the MotoGP event in 2023 at the Mandalika Circuit, but there is a possibility that they will watch it again in the following years if they see that there is a better development of the organizing system at the Mandalika Circuit. (4) A total of four respondents admitted to renting a passing pick-up car to reach the parking location, as many as six respondents admitted to using impromptu ojek services from local residents who had motorbikes, and as many as five respondents admitted to walking quite a distance before getting a ride from an impromptu ojek. that have sprung up in the Mandalika Circuit area. (5) A total of four respondents who are natives of Lombok gave their opinions regarding alternatives that the committee could take at the 2023 Mandalika MotoGP.